Periosteal pedicle graft with coronally advanced flap and its comparison with modified coronally advanced flap in the treatment of multiple adjacent gingival recessions-a randomized clinical trial - Swet Nisha; Pratibha Shashikumar (Elsevier, 2021)
The present study aimed at evaluating clinical utility of periosteal pedicle graft with coronally advanced flap (PPG ​+ ​CAF) vs modified coronally advanced flap (M-CAF) in cases of multiple adjacent gingival recessions involving maxillary and mandibular anteriors labially. Random allocation of 40 patients with 269 gingival recessions was done into two groups. In Test group (20 patients) periosteal pedicle graft followed by coronally advanced flap (PPG ​+ ​CAF) technique was performed and in control group (20 patients) modified coronally advanced flap (M-CAF) was attempted. Primary outcome measures included percentage root coverage (PRC), gingival thickness (GT), probing depth (PD), clinical attachment level (CAL), recession depth (RD) and width of keratinized gingiva (WKG). Secondary outcomes measures were patient centred outcomes, plaque index (PI) and gingival index (GI). Patients were recalled at baseline, 3,6 and 18 months postoperatively. Results: There was a significant decrease in the mean recession depth from 3.58 ​± ​0.53 ​mm (baseline) to 0.22 ​± ​0.01 ​mm (18 months) in PPG ​+ ​CAF test group and 3.7 ​± ​0.56 ​mm (baseline) to 0.21 ​± ​0.01 mm (18 months) in M-CAF control group. With 85% root coverage in test group and 78% root coverage in control group, the difference was statistically significant at 18 months. The test group showed significant higher clinical attachment level gain and increase in width of keratinized gingiva as compared to control group. Conclusion: In both the study groups PPG ​+ ​CAF and M-CAF, significant root coverage was achieved. However, in terms of increase in width of keratinized gingiva, gingival thickness and percentage root coverage, PPG ​+ ​CAF group presented significantly better results than M-CAF group at 18 months follow up. Thus, periosteum can be used as a pedicle graft along with coronally advanced flap as an alternative method in achieving better results with minimal cost.